Fog as a kind of water-substancein Belarusian phraseological world-view (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Based on the material of Belarusian phraseological units with the component туман ‘fog’, listed in literary and dialectal phraseological sources, the article singles out their characteristic cultural connotation and the stable evaluative contents of Belarusian culture that they hand down and preserve, its categories and senses, connected with fog as the name for water as a kind of substance. The author identifies the interaction between the language and national culture through phraseological units, which partially represent the concept “water” as one of the components of phraseological world view of the Belarusians in the diapason of cultural and national self-awareness, objectifying generally the natural and spatial codes of the culture.The authors points out that the phraseological units with the component туман (fog) and its derivative туманить most often convey a negative connotation: they reflect some special activities, ways and means for deceiving and conning people, showing off, misleading, inability or unwillingness to see the real world as it is, or maybe living in fool’s paradise. This all is related to the selection of the component-lexeme туман (fog) that has certain symbolic meanings assigned to it – ambiguity, inaccuracy, lies or chimeras, etc. Linguistic and cultural analysis of phraseological units with the component туман (fog) is carried out with the aim to determine the cultural information that has been recorded in them and handed down to new generations, the moral and ethical norms and codes of conduct, people’s relations that the Belarusians either consider to be laudable or reject and condemn. The subject of the research is the peculiarities of arrangement and ways of conveying cultural information, the contents of the “language” of culture based on the notion of fog with the aim of reconstructing the concept “water”, the integrity of which is impossible without taking into consideration all the “water” components in phraseological units that objectify the concept “water”. One of these components is the lexeme туман (fog), which is a part of the thematic group “kinds of water”.
Keywords: phraseologicalunit; component; fog; image; natural code of the culture; symbol; reference sample; stereotype